Different Ways to Become a Soviet Sinologist: A Note on personal choices - Kuznetsov, Marina (Mongolian Journal of International Affairs, 2015)
It is and always was an uneasy path for a Western scholar to become a sinologist. In the current research there were included interviews of 33 Russian sinologists. To analyze the value of different components in the process to become a sinologist there were chosen few major factors in the family and social background, early years and education. In half of the cases decision to go for Chinese studies was taken under the temporary circumstances during admission or studies at universities, and wasn’t a result of strong personal interest. This situation was tightly connected with the politics in the USSR, when in late 1940-s and early 1950-s it was decided to prepare big number of sinologists to help Chinese modernization. Mongolian Journal of International Affairs Vol.19 2014: 166-177